Mitochondrial Sequence Variation, Haplotype Diversity, and Relationships Among Dromedary Camel-Types - Alaqeely, Randa; Alhajeri, Bader H.; Almathen, Faisal; Alhaddad, Hasan (Frontiers in Genetics, 2021)
Dromedary camels are outstanding livestock that developed efficient abilities to tolerate desert conditions. Many dromedary camel-types (i.e., named populations) exist but lack defined specific breed standards, registries, and breeders’ governing organizations. The breed status of dromedary camel-types can partly be assessed by exploring mitochondrial DNA (mtDNA) variation. Accordingly, this study aimed to examine the breed status and the inter-population relationships of dromedary camel-types by analyzing sequence variation in the mtDNA control region and in three coding genes [cytochrome b, threonine, and proline tRNA, and part of the displacement loop (D-loop)] (867 bp region). Tail hair samples (n = 119) that represent six camel-types from Kuwait were collected, extracted, sequenced, and compared to other publicly available sequences (n = 853). Within the sequenced mitochondrial region, 48 polymorphic sites were identified that contributed to 82 unique haplotypes across 37 camel-types. Haplotype names and identities were updated to avoid previous discrepancies. When all sequences were combined (n = 972), a nucleotide diversity of 0.0026 and a haplotype diversity of 0.725 was observed across the dromedary-types. Two major haplogroups (A and B) were identified and the B1 haplotype was predominant and found in almost all dromedary-types whereas the A haplotypes were more abundant in African regions. Non-metric multidimensional scaling revealed an increased similarity among Arabian Peninsula “Mezayen” camel-types, despite their defining coat colors. The relationships among dromedary camel-types can partly be explained by mtDNA. Future work aimed at a deeper understanding of camel-type breed status should focus on a high number of nuclear markers.